Analysis of Vowel Sounds Errors in Arabic Conversation Modern Islamic Boarding School Muhammadiyah Daarul Khoir Gunungkidul Students - Hakim, Farid Rochman (Universitas Muhammadiyah Yogyakarta, 2023)
This study aims to determine the form of errors in the vowel sounds of Arabic words in the Arabic conversation of students at the Modern Muhammadiyah Islamic Boarding School Daarul Khoir Gunungkidul and to determine the factors that cause the occurrence of vowel errors. This research is a descriptive qualitative research. Data obtained by observing and interviewing students. The results of this study are four vowel errors, namely the change in vowel a to u. There is also a change in the vowel sound i to e. In addition, there were also errors in long vowel sounds which were pronounced short, even so short vowel sounds were pronounced long. The factors causing the error were that some students had not mastered Arabic rules correctly, made pronunciation easier, efficiency in pronunciation and the lack of students listening to Arabic words and sentences.